2018
DOI: 10.1177/1748895818800744
|View full text |Cite
|
Sign up to set email alerts
|

Minor harassments: Ethnic minority youth in the Nordic countries and their perceptions of the police

Abstract: As different social groups are directly and indirectly confronted with diverse forms of police practices, different sectors of the population accumulate different experiences and respond differently to the police. This study focuses on the everyday experiences of the police among ethnic minority young people in the Nordic countries. The data for the article are based on semi-structured interviews with 121 young people in Sweden, Norway, Finland and Denmark. In these interviews, many of the participants refer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
(48 reference statements)
0
19
0
7
Order By: Relevance
“…Our study belongs to the Nordic project 'Perceptions of procedural justice among ethnic minority youth in Denmark, Norway, Finland, and Sweden', funded by the Scandinavian Research Council for Criminology. A team of Nordic researchers have collected qualitative data on ethnic minority youth's experiences of the police and started to analyze them from various angles (Solhjell et al 2018;Birk Haller et al 2018). Previous research in Nordic countries and elsewhere has shown that young people living in socially disadvantaged areas and belonging to ethnic minorities typically experience police interactions more often and more negatively than others.…”
Section: Background and Analytical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study belongs to the Nordic project 'Perceptions of procedural justice among ethnic minority youth in Denmark, Norway, Finland, and Sweden', funded by the Scandinavian Research Council for Criminology. A team of Nordic researchers have collected qualitative data on ethnic minority youth's experiences of the police and started to analyze them from various angles (Solhjell et al 2018;Birk Haller et al 2018). Previous research in Nordic countries and elsewhere has shown that young people living in socially disadvantaged areas and belonging to ethnic minorities typically experience police interactions more often and more negatively than others.…”
Section: Background and Analytical Frameworkmentioning
confidence: 99%
“…Some individuals become 'permanently suspect' and the police start thinking that they 'process "the same dross", "the same losers" again and again' (ibid.). The police in Norway and Sweden are sometimes said to not inform ethnic minority youth of the reasons for being stopped and searched, and there is a strong conviction among them that they are both targeted (Sollund 2006;Mulinari 2017) and subjected to recurring harassments (Birk Haller et al 2018). Pettersson (2013Pettersson ( , 2014 also reports that young people with ethnic minority backgrounds who live in socially disadvantaged areas in Sweden repeatedly complain about the police being discriminatory.…”
Section: Background and Analytical Frameworkmentioning
confidence: 99%
“…Denne studien belyser koblingen mellom sosial identitet og ulike, men hyppige politimøter. I den større nordiske studien (Haller et al, 2018;Solhjell, Saarikkomäki, Haller, Wästerfors, & Kolind, 2019;Wästerfors & Burcar Alm, 2019) fant vi at saerlig unge menn opplevde at de hyppige politimøtene gjorde at de var nødt til å tenke på seg selv som en trussel for den etnisk nordiske majoriteten fordi de stadig ble assosiert med politi og kriminalitet. I dette fokuset på skoler i Oslo øst og sør er det spesielt sammenhengen mellom etnisk mangfold, relativt større fattigdom sammenlignet med andre bydeler og frekventering av politi som utgjør et stigma.…”
Section: Diskusjonunclassified
“…Samtidig er noe av det underliggende felles, nemlig at det er snakk om bydeler med høy andel minoriteter der unge møter politi jevnlig i tilstedevaerelse, kontrollsituasjoner eller hendelser. Den nordiske forskningen er relativt liten, men det er mye som tyder på at minoriteter i større grad blir kontrollert, og at det ofte er mer negative erfaringer i samfunn som ellers preges av eksepsjonell høy tillit til politiet (Haller et al, 2018;Holmberg & Kyvsgaard, 2003;Kääriäinen & Niemi, 2014;Pettersson, 2013;Solhjell et al, 2019;Sollund, 2007). Selv om disse møtene kan vaere vidt forskjellige, er de likevel relevante for å forstå opplevd rettferdighet som igjen påvirker synet på tillit til politiet.…”
Section: Diskusjonunclassified
“…The issues brought up by SJW vary, but their main concern is usually about social problems plaguing a country, like equality of gender rights (Gundy, 2014), minority issues (Haller et al, 2018;Madon et al, 2017), and human rights (Craig, 2012). The above problems are very closely related to the sentimentalism of moralism that was initiated by David Hume.…”
Section: Introductionmentioning
confidence: 99%